Anaerobic treatability of distillery spentwash - Isa, M.H.; Farooqi, I.H.; Khurshid, A. (1999)
This study is an attempt to delineate the effect of distillery spentwash on methanogenesis; and to ascertain the feasibility of using a single-stage or a two-stage reactor configuration. The results show that the spentwash contains both stimulatory as well as toxic substances. The stimulation of methanogenesis in a single-stage reactor shows its efficacy.